Grid resolution assessment method for hybrid RANS-LES in turbomachinery. Issue 1 (31st December 2022) - Li, Ruiyu; Zhao, Lei; Ge, Ning; Gao, Limin; Ni, Mingjiu
Abstract : Hybrid RANS-LES is a promising method for analyzing the complex flow structure in turbomachinery due to its excellent compromise between accuracy and computational cost. However, it is challenging to employ the existing URANS and LES grid resolution evaluation approaches in a hybrid RANS-LES simulation, thus commonly the required grid resolution is unknown, increasing the risk that LES relies on overly coarse grids and leading to unreliable predictions. Hence, spurred by this deficiency and driven by the aspects of coupling grid resolution evaluation with the interest quantity during turbomachinery design and mechanism analysis, this work proposes a novel grid resolution evaluation method suitable for both LES and URANS. The suggested technique considers three grid resolution criteria: no effects on the time-averaged flow field, major unsteadiness, and minor unsteadiness. The developed method is verified employing a classic scenario, i.e. Pitz-Daily backward-facing step. Furthermore, we demonstrate our method's applicability through a T106A turbine cascade example, confirming the feasibility and reliability of the proposed scheme. When applied to hybrid RANS-LES turbomachinery simulations, the research results highlight our method's capability to reduce uncertainty and improve reliability during gridding.